2000
DOI: 10.1063/1.125617
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen plasma effects on sol-gel-derived lead-zirconate-titanate thin films

Abstract: We studied effects of oxygen plasma treatment on the ferroelectric Pb(Zrx,Ti1−x)O3 (PZT) films prepared by a sol-gel method. Electrical characteristics of the films were found to be improved considerably by exposure to the O2 plasma, with enhanced remanent polarization and decreased leakage current densities. Chemical bonding analysis by means of x-ray photoelectron spectroscopy in the Pb 4f region indicated that the intensity from the perovskite PZT phase increased considerably after the O2 plasma treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…16,17 Low-temperature oxygen plasma etching is employed as a milder method for removal of organic components from bulk hybrids 18 and surface layers. [19][20][21][22][23] We have shown that the surface sol-gel process is an excellent chemical method for the fabrication of polymer/metal oxide nanocomposite films. 24,25 The organic moieties in such composite films may be readily removed by the oxygen plasma treatment.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Low-temperature oxygen plasma etching is employed as a milder method for removal of organic components from bulk hybrids 18 and surface layers. [19][20][21][22][23] We have shown that the surface sol-gel process is an excellent chemical method for the fabrication of polymer/metal oxide nanocomposite films. 24,25 The organic moieties in such composite films may be readily removed by the oxygen plasma treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that extra oxygen ions introduced by the plasma treatment can modify the chemical bonding of the lead atoms, transforming the metallic lead into the PZT phase. 10 In this study, the above scenario is more pronounced than the case of crystallized films, because the as-deposited SBTN may have more metallic bismuth states along with metallic bismuth by argon ion bombardment. Thereby, oxygen treatment can passivate the oxygen defects at the interface between the SBTN and platinum or at grain boundaries in the film.…”
Section: Discussionmentioning
confidence: 82%
“…Magnesium diboride powder, purchased from Aldrich Co. (99.998%), was pressed into a pellet, and oxygen and hydrogen plasma treatments were carried out with a microwave power of 120 W at a pressure of 50 Pa for 1 and 2 h [16,17]. X-ray diffraction (XRD) was performed before and after the plasma treatments by using a MAC Science diffractometer with CueK a radiation (l ¼ 0.154056 nm).…”
Section: Methodsmentioning
confidence: 99%